Pengaruh Kemampuan Literasi Digital Terhadap Efikasi Diri dan Kemandirian Belajar Siswa - Fadlilatul Amin; Nur Khasanah; Chusnul Adib Achmad (BIO-EDU: Jurnal Pendidikan Biologi, 2023)
The existence of digital technology in education requires digital literacy so that technology can be used optimally. Self-efficacy and student learning independence are very important for students to support learning. The purpose of this research is to describe the effect of digital literacy skills on students' self-efficacy and learning independence. This research is a type of quantitative research. The sampling technique uses a saturated sampling technique with a population of class XI IPA 1 and 2 MA Futuhiyah Jeketro and data collection uses a questionnaire. Testing the hypothesis using the regression test and test the coefficient of determination. The results showed: 1. Digital literacy skills have an effect on self-efficacy with a significance of 0.001 <0.05 and a large effect of 27.7%; 2. Digital literacy skills affect student learning independence with a significance of 0.031 <0.05 and a large influence of 12%.